Towards the construction of health workforce metrics for Latin America and the Caribbean - Carrasco Victor V; Ruiz Fernando F; Machado Maria H; Nigenda Gustavo G; Moliné Patricia P; Girardi Sabado S (BMC, 2011)
Abstract Introduction One of the components of the Health Observatory for Latin American and the Caribbean (HO-LAC) is the design and implementation of metrics for human resources for health. Under the HO-LAC initiative, researchers from nine countries in the region formed the Collaborative Community on Human Resources for Health in Latin America and the Caribbean to identify common metrics applicable to the field of human resources for health (HRH). Case description The case description comprises three stages: a) the origins of an initiative in which a non-governmental organization brings together researchers involved in HRH policy in LAC, b) a literature search to identify initiatives to develop methods and metrics to assess the HRH field in the region, and c) subsequent discussions held by the group of researchers regarding the possibilities of identifying an appropriate set of metrics and indicators to assess HRH throughout the region. Discussion and evaluation A total of 101 documents produced between 1985 and 2008 in the LAC region were identified. Thirty-three of the papers included a variety of measurements comprising counts, percentages, proportions, indicators, averages and metrics, but only 13 were able to fully describe the methods used to identify these metrics and indicators. Of the 33 articles with measurements, 47% addressed labor market issues, 25% were about working conditions, 23% were on HRH training and 5% addressed regulations. Based on these results, through iterative discussions, metrics were defined into three broad categories (training, labor market and working conditions) and available sources of information for their estimation were proposed. While only three of the countries have data on working conditions, all countries have sufficient data to measure at least one aspect of HRH training and the HRH labor market. Conclusions Information gleaned from HRH metrics makes it possible to carry out comparisons on a determined experience in space and time, in a given country and/or region. The results should then constitute evidence for policy formulation and HRH planning and programs, with improved health system performance ultimately contributing to improved population health. The results of this study are expected to guide decision making by incentivizing the construction of metrics that provide information about HRH problems in LAC countries.